Implementers’ tool for analyzing the enabling environment to enhance the scaling of irrigation and water management tested in Ethiopia, Ghana, Mali, and Nepal - CGIAR Research Program on Water, Land and Ecosystems (2021)
This enabling environment analysis tool was developed and applied to identify systemic barriers to and opportunities for scaling farmer-led irrigation in Ethiopia, Ghana, Mali and Nepal. It informed the World Bank’s farmer-led irrigation guide.